ANALYSIS OF CONSUMER PREFERENCES FOR PURCHASING WINGKO BABAD CAP KERETA API IN SEMARANG CITY - Syifa Yumna Maghfiroh; Achma Hendra Setiawan (Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This study aims to analyze the relationship between each product attribute and the purchase frequency of Wingko Babad Cap Kereta Api in the city of Semarang. The product attributes in question are flavor, price, packaging, and brand loyalty. The determination of the sample size uses the Lemeshow formula because the size of the population is not precisely known. The sampling method used non-probability sampling through the accidental sampling technique, resulting in 100 respondents. The collection of respondent data was conducted using questionnaires and interviews. The collected data were analyzed using the Chi-Square Test with the help of SPSS version 25. The research results show that flavor, price, packaging, and brand loyalty have a significant relationship with the purchase frequency of Wingko Babad Cap Kereta Api in the city of Semarang. Consumer preferences regarding these four product attributes are not the same. Consumers will make a purchase if each attribute of the Wingko Babad Cap Kereta Api product is considered better compared to other brands of wingko babad. Based on the product attributes, consumer preference is for Wingko Babad with the right texture and level of sweetness, an affordable price that matches its quality, packaging that is easy to carry and has an attractive design, and a brand that is popular and better than other brands.